Good Amil Governance (GAG) and Efficiency of Zakat Institution in Indonesia - Ninglasari, Sri Yayu; Mirzal, Husnul; Majid, Rifaldi; Ulya, Badriyatul; Himmawan, M. Fikri (Ijtimā iyya Journal of Muslim Society Research, 2023)
This study aims to analyze the implementation of Good Amil Governance (GAG) in zakat management organizations (OPZ) and the efficiency of zakat distribution in Indonesia. This study uses a qualitative method with a literature study approach through secondary data tracing in the annual reports of zakat management organizations, journals, books and the official website of OPZ in Indonesia. The results showed that most of the OPZ had implemented the GAG principles thoroughly. In addition, the problem of inefficiency in the distribution of zakat in Indonesia has been overcome by the National Amil Zakat Agency (BAZNAS) through the issuance of the decision of the chairman of BAZNAS No. 33 of 2019 through identification of the Mustahik Identification Number (NIM). This research is expected to have implications for improving the application of governance and coordination of zakat distribution by OPZ in Indonesia.